The Effect Of Dietary Approach To Stop Hypertension (Dash) Counseling On Reducing Blood Pressure - Siti Nur Luthfiana; Arwani Arwani; Budi Widiyanto (JENDELA NURSING JOURNAL, 2019)
Background: Hypertension is an increase blood pressure through arterial contractions which complicate stroke and heart. Hypertension explains by high salt consumption habits, smoking, obesity, stress, and alcohol which are at risk of death. In addition, the habit of consuming anti-hypertensive drugs results in kidney and liver damage to control hypertension by choosing a healthy diet DASH diet.Purpose: This study purpossed to find the effect of diet DASH counseling on reducing blood pressure in patients with hypertension.Methods: The study design used queasy experimental with a pre-post test non equivalent control group. The sample of this study was 46 hypertensive primary clients, 46 people explain into intervention and control groups with purposive sampling technique. The instruments used were booklets and sphygmomanometers. Interventions were given 3 times for 1 week then continued mentoring every day for the next 3 weeks. Data analysis used the Wilcox test and the Mann Whitney test. Results: The results showed that there was a reduction from dietary approach to stop   hypertension (dash) counseling on blood pressure in hypertensive patients significantly with a difference in the mean difference of 0.0215 for systole and 0.0232 for diastole.Conclusion: Dash diet counseling can reduce blood pressure in patients with hypertension.